Colorimetric Determination of Uric Acid in Live samples (Indian Journal of Forensic Medicine & Toxicology, 2020)
A simple, sensitive and precise colorimetric method for uric acid determination was described. The method based on the complexion reaction between uric acid, potassium ferricyanide, and ferric chloride in hydrochloric acid medium to form blue colored charge transfer complex measured at maximum wavelength 752 nm. The optimum conditions obtained were volume 0.3 ml for hydrochloric acid, 1.25 ml for both potassium ferricyanide and ferric chloride solutions, 60?C and 8 minutes as maximum temperature and time of reaction, the order of mixing additives was uric acid, ferric chloride, potassium ferricyanide, and hydrochloric acid. The highly accurate and precise results obtained with RSD%, Recovery%, Ere%, and D.L were (0.755 to 4.376), (99.676 to 97.831), (-0.033 to -2.169), and 0.1569 µg mL-1 respectively, the calibration graphs were linear in the concentration range of (2.0-200µg ml-1), the . molar absorptivity (5937.473L mol-1 cm-1) The proposed methods were successfully applied for the determination of uric acid in serum and urine samples for twenty persons.